Knowledge and uptake of folic acid among pregnant women attending a secondary health facility in Ibadan (2017)
Background: Folate deficiency is associated with poor pregnancy outcomes and is one of the most common vitamin deficiencies in women, especially those of reproductive age. Aims: This study aimed to determine the level of knowledge and uptake of folic acid among a sample of pregnant women. Method: A descriptive cross-sectional study, using a structured questionnaire, was carried out among 300 pregnant women attending antenatal clinics in one hospital in Oluyoro, Ibadan, Nigeria. Findings: All participants claimed to have heard of folic acid and major source of information was health workers (77.3%). Only 11.8% knew that folic acid can prevent birth defects and just 22.7% knew the best time to start using folic acid. Almost all the women (98.3%) reported using folic acid in the current pregnancy, of whom 54.2% used it as prescribed. Education (P=0.002), marital status (P=0.001), plan of pregnancy (P=0.022), and maternal age (P=0.046) were significantly associated with knowledge of folic acid. Employment status was significantly associated with uptake of folic acid (P=0.004). Conclusions: In this study, knowledge and uptake of folic acid was low among young, single and low education status women. Campaigns promoting periconceptional use of folic acid will be very useful in reaching women of child-bearing age particularly those pregnant and not registered for antenatal care.